(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Asyiah IN, Mudakir I, Hoesain M, Pradana AP, Djunaidy A, Sari RF. 2020. Consortium of endophytic bacteria and rhizobacteria effectively suppresses the population of Pratylenchus coffeae and promotes the growth of Robusta coffee. Biodiversitas 21: 4702-4708. Pratylenchus coffeae as the coffee-parasitic nematode can cause a yield loss from 28.7% to 78.4% on Robusta coffee (Coffea canephora A. Froehner). Environmentally friendly and sustainable efforts can be made to control this nematode by applying the antagonistic agents from the bacterial group. The application of antagonistic agents in a consortium has a better effectivity than a single application. This study was aimed to identify the effectivity of the consortium of endophytic bacteria and rhizobacteria formulated on a cost-effective molasse medium against the P. coffeae population and growth of Robusta coffee in a greenhouse. A total of nine bacterial isolates of genus Bacillus and Pseudomonas were used during experiment. The formulation was prepared by mixing the bacterial suspension and 2% molasses with a ratio of 1:1 (v/v). The greenhouse assay was performed following the completely randomized block design pattern with five treatments and five replications. Robusta coffee plant clone BP 936 was treated with a 10 mL (109 CFU mL-1) bacterial consortium mixture while control was treated with 10 mL sterilized water. Each plant was inoculated with P. coffeae 50 J2 after a week of bacterial consortium application. The result showed that all bacterial consortiums were effective in suppressing the population of P. coffeae in soil and root of Robusta coffee. All consortiums gave a better result than control in suppressing the population of P. coffeae. The best suppression of nematodes was shown by the Cst 02 consortium with the suppression value of 62.5% in the root and 76.1% in the coffee plant rhizosphere. The application of bacterial consortium increases the plant height (28.02-44.51%), number of leaves (127.27-168.18%), and leaf area (278.8-425.57%). In this study, suppression of P. coffeae population by bacterial consortium showed a positive correlation with plant growth. This study presents the information of endophytic bacteria and rhizobacteria consortium from Bacillus and Pseudomonas group that is effective in suppressing the population P. coffeae and improves the growth of Robusta coffee.